STAIN MANDAILING NATAL PUBLIC COMMUNICATION IN THE APPLICATION OF FACE-TO-FACE LEARNING DURING THE COVID-19 PANDEMIC - Farid, Ahmad Salman (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2021)
The application of face-to-face learning during the Covid-19 pandemic needs to be conveyed appropriately to the public so that it requires public communication. The applicable face-to-face meeting policy needs to be reviewed so that there are no errors in the delivery of messages and feedback received by STAIN Mandailing Natal. This study aims to find out how the public communication of STAIN Mandailing Natal in the application of face-to-face learning during the Covid-19 pandemic with a qualitative descriptive method. The description of the research results shows that the public communication conducted by STAIN Mandailing Natal from the aspect of openness, the challenge is that it is difficult to convince students to maintain health protocols. STAIN Mandailing Natal has used Facebook, Whatsapp and the website as an option to communicate with students. The stakeholders collaborate in communication with various parties including the head of the study program, coordination across student associations of the study program and is carried out directly.